Lean Manufacturing through VSM and SMED for Waste Reduction in Paper-Based Packaging - Yumeling; Suharjito (Advance Sustainable Science Engineering and Technology, 2026)
This study analyzes the reasons for waste in the production processes of a paper-based food packaging company in Indonesia and proposes improvement measures to make the operations more efficient. Through the application of Value Stream Mapping (VSM) and Single-Minute Exchange of Dies (SMED), three significant waste categories were charted: product defects (24.74%), unnecessary movements (22.23%), and unnecessary inventory (13.29%). Implementation of SMED successfully reduced the time of tool change from 60.24 minutes to 27.12 minutes, a setup time improvement of 54.98%. Pursuit of labeling system improvement as well as putting in place a Just-In-Time (JIT) inventory practice also played an important role in the reduction of wastes and fast responsiveness. Consequently, Process Cycle Efficiency (PCE) increased from 70.37% to 73.41%, production capacity increased by 1,241 units per cycle, and complaint counts for defective products declined appreciably over a period of six months. These results underscore the actual benefits of Lean methods and underscore the standard for performance excellence for the same pursuit of sustainable operational excellence within the same industry.